Team Incentives and Performance: Evidence from a Retail Chain - Guido Friebel; Matthias Heinz; Miriam Krüger; Nikolay Zubanov (Institute for the Study of Labor (IZA), 2015)
We test the effectiveness of team incentives by running a natural field experiment in a retail chain of 193 shops and 1,300 employees. As a response to intensified product market competition, the firm offered a bonus to shop teams for surpassing sales targets. A bonus to teams rather than individuals was a natural choice because the firm does not measure individual performance and relies on flexible task allocation among employees. On average, the team bonus increases sales and customer visits in the treated shops by around 3%, and wages by 2.3%. The bonus is highly profitable for the firm, generating for each bonus dollar an extra 3.80 of sales, and 2.10 of operational profit. The results show the importance of complementarities within teams and suggest that improved operational efficiency is the main mechanism behind the treatment effect. Our analysis of heterogeneous treatment effects offers a number of insights about the anatomy of teamwork. The firm decided to roll out the bonus to all of its shops, and the performance of treatment and control shops converged after the roll-out.
Keywords: J3; L2; M5; 330; management practices; randomized controlled trial (RCT); natural field experiment; insider econometrics